The role of currency derivatives in across countries portfolio risk management: A case of international stock portfolio diversification. - Liu, Miou (2007)
The power of international portfolio diversification in reducing risk is widely practiced by investors. Since the internationalization of security portfolios, there is an additional risk, and it is known as foreign exchange risk. Hedging currency exposure greatly enhances the diversification of investment return. This paper investigates the impact of currency derivatives on the international diversified stock portfolio, and explains how hedging works. Several issued are covered in this paper: 1) the benefit of international diversification; 2) the problems of currency exposure and the techniques of hedging using currency derivatives; 3) the motivation of hedging activity of financial risk management; 4) investigating the role of currency derivatives in internationally diversified stock portfolio. The results in this paper show the benefits of currency hedging of international stock portfolios are not consistent in different period. The performance of portfolio was enhanced through hedging during period of 1997 to 2002. However, the unhedged portfolios had performed better than hedged portfolio for the period between 2003 and 2007.